Chronic strains, self-efficacy, and mental health: a cross-sectional study among university students in Bangladesh - Hossain, Rashed; Nasir, Rasheda Irshad (Intelektual Pustaka Media Utama, 2025)
Chronic strains, arise from daily activities, can affect mental healthcare of individuals across various professions, including students. However, how chronic strains affect mental health of students is poorly understood so far for students. We aim to identify the most prevalent chronic strains and examine the effects of chronic strains on mental health conditions adjusted for socio-demographic variables. A total of 393 students were included in the study. They were interviewed through a structured questionnaire between April 6 and May 28, 2023. The outcome variable considered were mental health measured through 14-item questions. The prime explanatory variable was chronic strains. Multivariable linear regressions were used to the relationships of chronic strains, self-efficacy, and socio-demographic characteristics with mental health conditions. We found that 16.7% of participants reported low levels of chronic strains, 66.4% reported moderate levels and 18.3% reported high levels. ‘Tension for future career’ emerged as the most significant source of stress that led chronic strains. Chronic strains and self-efficacy were found to be significant determinants of different mental health conditions. These findings suggest that institutions should focus on improving students’ psychological well-being to mitigate the impact of chronic strains.